Piecing the puzzle: Addressing the multi-payer and fragmented health financing system in the Philippines - Ida Marie Pantig; Valerie Gilbert Ulep (Philippine Institute for Development Studies (PIDS), 2025)
In this report, we characterize the government health expenditures, examine the fragmented and overlapping nature of different financing streams, and propose a framework to address these challenges. In the past decade, the Philippines has experienced unprecedented growth in government health expenditures, driven by growing fiscal space, policy prioritization towards health, and rising national income. While this trend is commendable, we observed growing fragmentation in the system despite consolidation attempts under the Universal Health Care (UHC) Act. Multiple financing streams, including PhilHealth, the country's national health insurance program, national and local government budgets, and medical assistance programs and subsidies in the form of patronages, often overlap and sometimes compete. This undermines efficiency and equity by risk pooling, limiting economies of scale, and leading to instances of "double funding."
Keywords: 330; Health Financing; Health Expenditure; Universal Health Care; National Health Insurance Program